2005
DOI: 10.1021/jm050251o
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Estrogenic Properties of Diphenols by the Incorporation of Ferrocene. Generation of Antiproliferative Effects in Vitro

Abstract: We report here the synthesis and the strong and unexpected antiproliferative effect of the organometallic diphenolic compound 1,1-bis(4'-hydroxyphenyl)-2-ferrocenyl-but-1-ene (4) on both hormone-dependent (MCF7) and -independent (MDA-MB231) breast cancer cells (IC(50) = 0.7 and 0.6 microM). Surprisingly, 6 [1,2-bis(4'-hydroxyphenyl)-2-ferrocenyl-but-1-ene], the regioisomer of 4, shows only a modest effect on these cell lines. This pertinent organometallic modification seems to trigger an intracellular oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(166 citation statements)
references
References 26 publications
4
162
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11][12] We have shown that some ferrocene derivatives are very active against cancer cells. The addition of a ferrocenyl moiety to selected polyaromatic phenols, [13][14][15][16] amines, 17,18 amides, 19 and esters 19,20 can potentiate their antiproliferative effects against breast and prostate cancer cells. For example, 4-hydroxytamoxifen, the active metabolite of the breast cancer drug tamoxifen, 21 shows limited cytotoxicity against hormone-refractory breast cancer cells (LC 50 for MDA-MB-231 cells:…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] We have shown that some ferrocene derivatives are very active against cancer cells. The addition of a ferrocenyl moiety to selected polyaromatic phenols, [13][14][15][16] amines, 17,18 amides, 19 and esters 19,20 can potentiate their antiproliferative effects against breast and prostate cancer cells. For example, 4-hydroxytamoxifen, the active metabolite of the breast cancer drug tamoxifen, 21 shows limited cytotoxicity against hormone-refractory breast cancer cells (LC 50 for MDA-MB-231 cells:…”
Section: Introductionmentioning
confidence: 99%
“…These features provide a versatile platform for drug design that is now being exploited in several areas. For example, the redox activity of the organometallic ferrocenylphenol substitutents enhances the anticancer activity of tamoxifen derivatives by conferring an ability to generate reactive oxygen species in cells (3). Here we consider the anticancer activity of ruthenium(II) arene complexes.…”
mentioning
confidence: 99%
“…[8] This cytotoxic effect is also observed with the diphenolic compound Fc-diOH (3). [9] We have found that the most effective compounds (IC 50 values less than 1 μM) possess, like 2 and 3, a ferrocene-ene-para-phenol entity. [10,11] The ferrocene appears to act as a stimulus for a mild intramolecular oxidation involving the phenol group, leading to the facile production of quinone methides, the formation, structure, and electrophilic behavior of which we have established.…”
Section: Introductionmentioning
confidence: 82%
“…[3] [h] Values from ref. [9] [i] Value from ref. [4] Relative Binding Affinities for the α Form of the Estrogen Receptor (ER) and Log P o/w of the Compounds…”
Section: Study Of Thementioning
confidence: 99%